2016
DOI: 10.1590/1807-3107bor-2016.vol30.0009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high energy X-ray irradiation on the nano-mechanical properties of human enamel and dentine

Abstract: Radiotherapy for malignancies in the head and neck can cause common complications that can result in tooth damage that are also known as radiation caries. The aim of this study was to examine damage to the surface topography and calculate changes in friction behavior and the nano-mechanical properties (elastic modulus, nanohardness and friction coefficient) of enamel and dentine from extracted human third molars caused by exposure to radiation. Enamel and dentine samples from 50 human third molars were randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 28 publications
0
31
0
6
Order By: Relevance
“…As previously shown, with radiation, the organic and mineral portions of dentin can be altered, consequently modifying its mechanical properties (1)(2)(3)13,28). It may be suggested that the association between these two factors could promote increased deleterious effects in the dentin of root filled teeth, since endodontic therapy can also cause changes in the mechanical properties of teeth as well (7).…”
Section: Discussionmentioning
confidence: 95%
“…As previously shown, with radiation, the organic and mineral portions of dentin can be altered, consequently modifying its mechanical properties (1)(2)(3)13,28). It may be suggested that the association between these two factors could promote increased deleterious effects in the dentin of root filled teeth, since endodontic therapy can also cause changes in the mechanical properties of teeth as well (7).…”
Section: Discussionmentioning
confidence: 95%
“…11 In this study, regardless of the final irrigation solution and root third, irradiated teeth had lower bond strength than non-irradiated ones, which is probably associated with changes in the dentin ultrastructure such as obliteration of dentinal tubules, 14,23 alterations in the intertubular, peritubular, and intratubular dentin, 14 and with the fragmentation of the network of collagen fibers of the dentinal tissue and its deproteinization. 9,13,14,24 It is suggested that head and neck radiation therapy may lead to alterations in the amide III group present in the collagen structure and result in disorganization of the secondary structure of the protein unit that forms the collagen fibers, 25 modifying the natural arrangement between mineral and organic contents of dentin, changing its physical and mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation-related caries is considered a chronic effect of RT and they affect both, cervical and occlusal surfaces of teeth. When those caries progress, the effects go from enamel cracks and cuspal wear to the destruction of the coronary structure [8,9]. A retrospective study showed a dose-response correlation between RT and tooth damage: minimal tooth structure damage happens below 30 Gy; the risk of tooth breakdown increases 2-3 times between 30 and 60 Gy due to the permanent damage of the salivary glands above 30 Gy; and the chance of tooth breakdown increases by 10 times above 60 Gy, suggesting radiation-induced damage to the tooth structure further to the reduced salivary flow [8,10].…”
Section: Introductionmentioning
confidence: 99%